Cognitive emotion regulation for improved mental health: A chain mediation study of Chinese high school students - Xue, Meijuan; Cong, Beile; Ye, Yiduo (Frontiers in Psychology, 2023)
High school is a critical time for individual development, during which significant physical and mental changes related to puberty occur. Therefore, high school students’ mental health requires more attention from schools, families, and society. Our study explored high school students’ present status and family functioning characteristics, psychological capital, cognitive-emotion regulation, and life satisfaction by surveying 917 students in China. Data were analysed using independent sample t-tests, one-way analysis of variance, regression analysis, structural equation modelling, and path analysis. Our results showed that family function was positively correlated with life satisfaction, psychological capital, and positive emotion regulation strategies. Negative emotion regulation strategies were inversely correlated with these variables. The variable of cognitive emotion regulation has two dimensions, positive and negative. Cognitive-emotional regulation and psychological capital had sequential mediating effects between family function and life satisfaction. The results of this study offer new explanations for the mechanisms of family functioning on life satisfaction, how family functioning affects life satisfaction via cognitive-emotional regulation and psychological capital, and have some implications for family parenting. It also provides critical theoretical and practical guidance for schools to emphasise the use of positive cognitive-emotional regulation and the development of students’ psychological capital levels in teaching and learning, thereby improving individual life satisfaction further. These findings highlight the importance of considering emotion regulation strategies and psychological capital when determining students’ life satisfaction, and ensuring a healthy family environment.